KONSEP RASA DALAM KEHIDUPAN MASYARAKAT JAWA - Katarina Indah Sulastuti (Institut Seni Indonesia Surakarta, 2012)
This paper discusses the concept of rasa/sense in Javanese society. Sense is a concept that is widely understood. The meaning is dependent on the text and contextual, that is related to the word sense of the term itself and understanding in the areas of individual and social area of life. Domains are related to the problems associated with devotional activities, the human relationship with the forces outside of themselves (the supernatural-in the realm of religion), on issues related to social activities (humans with each other-in the realm of ethics) and the issue of aesthetics, as activities related to the issue of reflection on; Sang supernatural, the natural environment, others and himself, through artistic expression. Key words : concept, sense, Javanese